Verification of Object Relational Maps - Rajamani, Sriram (2007)
Enterprise software systems need to deal with two dominant data models. While object oriented languages (such as Java, C#, C++) are the dominant ways to write business logic, relational databases are the dominant ways to store data. Object-Relational (OR) maps are widely used to mediate between these two data models. We present a system to verify correctness of OR maps. We formulate simple correctness conditions for OR maps, and convert these conditions to validity of formulas in first order logic. We have built a verification tool called ROUNDTRIP that is able to both validate and find errors in OR maps defined in the ESQL language of the Microsoft EDM data model.